(untitled) (Journal of Chemical Engineering, 2012)
Starch is an inexpensive abundant product and is totally biodegradable in a wide variety of environments and allows the development of totally degradable products for specific market needs. We study the influence of starch on the degradation behavior of plastic films prepared by mixing the film grade polyethylene pellets with different amounts of starch. The mechanical strength of the polymer films were measured by Instron 5560 Tensile Testing Machine and observed that with the addition of starch mechanical strength decreases. As biodegradation rate increases with starch addition, 25 to 35% starch can be added safely in the plastic shopping bag without changing its strength significantly. DOI: http://dx.doi.org/10.3329/jce.v26i1.10180 JCE 2011; 26(1): 38-40